Fluoranthene induced changes in photosynthetic pigments, biochemical compounds and enzymatic activities in two microalgal species: Chlorella vulgaris Beijerinck and Desmodesmus subspicatus Chodat - Patel, Miral; Kumar, JI Nirmal; Tiwari, KK (International Journal of Environment, 2014)
The photosynthetic pigments, biochemical and enzymatic activities in two freshwater microalgal species, Chlorella vulgaris and Desmodesmus subspicatus at different fluoranthene concentrations were compared with the control conditions. During 16-days of incubation period when treated with fluoranthene, both microalgal species exhibited variable amount of photosynthetic pigment, biochemical compounds and enzymatic activities. The addition of fluoranthene at concentrations ranged from 1.5 mg l-1; to 10 mg l-1; to microalgal cultures led to changes in all different metabolites but the patterns varied from species to species. Among the two species tested, pigment, biochemical and enzymatic contents were remarkably declined from 7 % to 95% in C. vulgaris. Moreover, all metabolites in D. subspicatus also diminishing significantly by 3% to 88% of fluoranthene doses (10ppm). These results suggest that fluoranthene-induced changes of pigments, biochemical and enzymatic variations in test microalgae, D. subspicatus and C. vulgaris, might reveal its resistance and ability to metabolize PAHs. At the same time, the PAH impact changes on different metabolic activities were higher at 12 and 16 days than at 4 and 8 days in treated microalgae. DOI: http://dx.doi.org/10.3126/ije.v3i1.9941 International Journal of Environment Vol.3(1) 2014: 41-55